مقاصد الشريعة الإسلامية في اختلاف عدد الميراث الإسلامي (دراسة مقاصدية نقدية) - Zuhratul Aini Mansur; Muhammad Royyul Ulum (Al-Zahra : Journal for Islamic and Arabic Studies, 2022)
The inheritance system in Islam has arrived at an increasingly complex time. There are suspicions raised by deniers and skeptics about the number of different inheritances that divided it because they do not understand and know about it and the religion of Islam is the right to understand. The research aims to find out the truth of the Islamic inheritance system and the opinions of scholars about its justice and explore the suspicions raised about the issue of male inheritance such as the luck of females and respond to them, as well as to know the purposes of Sharia in the difference in the number of inheritances between male and female. Where the research used the critical approach on Maqasid Syariah by making its investigations divided into the introduction, which contains the background of the research and its identification and previous studies; The first section dealt with knowing the truth of the inheritance system, the second section talked about investigations in the legitimate purposes, and the third section talked about the legitimate purposes in the difference in the number of inheritance and the suspicions raised about it and responding to them. The results of this research is that the inheritance system is one of the fairest of all systems in the world and the purposes of Sharia as a means of understanding the texts of Sharia rulings and to refute the suspicions raised on the subject.